1983
DOI: 10.1007/bf02787436
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of fatty imidazolines and their N‐(2‐aminoethyl) derivatives

Abstract: Cationic high molecular weight surfactants hold promise as water repellents for soil for water harvesting. Specifically, the products of the reaction of 2 moles of fatty acids with 1 mole of diethylenetriamine were investigated. Optimum conditions for the formation of imidazolines as well as the open-chain N-(2-aminoethyl) derivatives, i.e., the diamides, were determined. Saturated fatty acids, pelargonic through behenic, oleic acid, elaidic acid as well as tallow, tallow fatty acids, and hydrogenated tallow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Thus, the primary amine is more reactive than the secondary amine in that the 1,3-diamides 5 are the main reaction products. Traditionally, formation of imidazoline compounds 7 from the 1,3-diamides 5 requires severe reaction conditions (high temperature and vacuum or long reaction times) (3,8,9). In the present work, when a highly dilute solution of 1 and 2 was used, amide formation took place with the more reactive secondary amine position, and the reaction proceeded probably by way of 1,2-diamides 6 (Scheme 1), which led to the imidazoline compounds 8 in good yield under mild reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the primary amine is more reactive than the secondary amine in that the 1,3-diamides 5 are the main reaction products. Traditionally, formation of imidazoline compounds 7 from the 1,3-diamides 5 requires severe reaction conditions (high temperature and vacuum or long reaction times) (3,8,9). In the present work, when a highly dilute solution of 1 and 2 was used, amide formation took place with the more reactive secondary amine position, and the reaction proceeded probably by way of 1,2-diamides 6 (Scheme 1), which led to the imidazoline compounds 8 in good yield under mild reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Even though no structural evidence is given, the preparation of compounds 3 and 4 is still claimed in recent patents (6,7). Other researchers have reported that the reaction of DETA with fatty acids does not take place in a 1:1 molar ratio; hence fatty acid monoamides 3 and the related imidazoline derivatives 4 are unlikely (3,4,8). Additionally, discrepancies exist in the literature over the mechanism of the reaction, in particular the relative reactivities of the primary and secondary amines (3,4,8,9).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Researchers [28] found out that tertiary amine content reduced on 5-8 % wt. in 18 months when stored in a closed container.…”
Section: Vacuum Effect On Alkylimidazoline Formationmentioning
confidence: 99%